Low permeability oil reservoir water plugging agent with biomimetic mineralization and preparation method thereof

Through the low-permeability reservoir water blocking agent of bionic mineralization, the combination of graft polymer and nano calcium carbonate is used to self-assemble to form organic-inorganic composite mineralized materials, solving the problem that the existing technology cannot effectively block high-water fractures in low-permeability oil fields and achieving excellent water blocking effect.

CN119752427APending Publication Date: 2025-04-04SINOPEC OILFIELD SERVICE CORPORATION +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411659546.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing technology cannot effectively seal the high-water-containing cracks in low-permeability oil fields, resulting in the same oil-water layer, unclear water effluent layer, small interlayer, poor permeability, and large water effluent cracks, which seriously affect the development and production of the oil field.

Method used

The low-permeability reservoir water blocking agent with bionic mineralization is used to mix graft polymers with nano-calcium carbonate, and polymer composites with larger molecular weight are generated by hydrogen bond self-assembly to guide the self-assembly and deposit of calcium ions, magnesium ions and carbonate ions in the formation water to form organic-inorganic composite mineralized materials, achieving the purpose of blocking the low-permeability water effluent layer.

Benefits of technology

This water blocking agent can selectively block strong water effluent cracks in low-permeability reservoirs, relieve contradictions that affect oil field production, and have excellent water blocking effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

The invention discloses a low permeability reservoir water plugging agent with bionic mineralization and a preparation method thereof. First, 1-chloroacetic acid and tetraethylenepentamine are used to prepare a polyamine polypeptide by polycondensation, 5-aminouracil and ethylene glycol diglycidyl ether are used to prepare an intermediate 1, p-aminocyclohexanone and ethylene glycol diglycidyl ether are used to prepare an intermediate 2, and an intermediate 3 is prepared by aminoethyl sodium hypophosphite and ethylene glycol diglycidyl ether, and then the intermediate is grafted to the polyamine polypeptide in proportion, and then mixed with nano calcium carbonate in clear water. The mixed system is self-assembled by hydrogen bonds in a low permeability formation aqueous solution to generate a polymer complex with a larger molecular weight. The polymer complex guides the nano calcium carbonate in the system, and the calcium ions, magnesium ions, and carbonate ions in the formation water to self-assemble and deposit to generate an organic-inorganic composite mineralized material, so as to achieve the purpose of plugging a low permeability water-producing layer. The preparation process of the water plugging agent is reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an oil reservoir water plugging agent, in particular to a low permeability oil reservoir water plugging agent with bionic mineralization. The invention also relates to a preparation method of the low permeability oil reservoir water plugging agent with bionic mineralization, and belongs to the technical field of oilfield production additives. Background Art

[0002] The effective exploitation of low-permeability unconventional oil and gas resources such as tight oil and shale oil is mainly based on the popularization of fracturing technology and low-permeability water injection technology, which has caused a large number of cracks in such oil fields, resulting in the sudden advance of injected water, a rapid increase in the water content of crude oil, and prominent phenomena such as oil and water in the same layer, unclear water-producing layer position, small interlayer, poor permeability, large water-producing cracks, and high pressure. The plugging of such oil layers requires plugging agents with low viscosity of the well fluid, high strength after cementation, and strong selectivity for water-producing cracks. Mechanical water plugging and conventional chemical water plugging technologies cannot effectively solve such problems, which seriously affects the development and production of low-permeability oil fields. Therefore, the development of a selective water plugging agent suitable for low-permeability and high-water-content fractured oil layers is a production need for most domestic oil fields at present.

[0003] Biomineralization refers to the process of forming inorganic minerals in living organisms. Through the regulation of specific organic templates, inorganic matter nucleates and slowly grows at the inorganic-organic interface, and finally an inorganic-organic composite material with a certain shape and structure is obtained. According to the characteristics of biomineralization, templates are used to simulate organic pre-organizations in biological organisms to prepare inorganic crystalline materials with specific multi-level structures. The essence of the biomimetic mineralization process is the process of regular clustering and precipitation of inorganic crystals (calcium carbonate, calcium phosphate, etc.) under the guidance of self-organizing biological molecules secreted by cells, including: first, the self-assembly of organic matter is formed on the surface of inorganic matter; then the inorganic precursor (Ca 2+ Mg 2+ Etc. and CO3 - 、SO4 2- A chemical reaction occurs at the interface between the self-assembled molecular film and the solution phase to generate inorganic microcrystals; finally, under the template of the self-assembled organic molecular system, the inorganic microcrystals are orderly clustered and precipitated to form an inorganic / organic hybrid, namely, a biomineralized material. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract of the specification of this application and the title of the invention, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] The primary purpose of the present invention is to overcome the problems existing in the prior art and provide a low-permeability oil reservoir water plugging agent with a bionic mineralization effect. The agent is mixed in clean water in a certain proportion, and the formed mixed system self-assembles through hydrogen bonds in the low-permeability formation water solution to generate a polymer complex with a larger molecular weight. The polymer complex guides the nano-calcium carbonate in the system and the calcium ions, magnesium ions, and carbonate ions in the formation water to self-assemble and precipitate, thereby generating an organic-inorganic composite mineralized material, thereby achieving the purpose of plugging the low-permeability water-producing layer.

[0007] In order to solve the above technical problems, the present invention provides a low permeability oil reservoir water plugging agent with bionic mineralization, which is mixed with a graft polymer and nano calcium carbonate, and the molecular formula of the graft polymer is:

[0008]

[0009] Where R1 is R2 is R3 is

[0010] Another object of the present invention is to overcome the problems existing in the prior art and provide a method for preparing a low-permeability oil reservoir water plugging agent with a bionic mineralization effect. The process is reliable. The prepared water plugging agent is mixed with clean water in a certain proportion. The formed mixed system self-assembles through hydrogen bonds in the low-permeability formation water solution to generate a polymer complex with a larger molecular weight. The polymer complex guides the self-assembly deposition of nano-calcium carbonate in the system and calcium ions, magnesium ions, and carbonate ions in the formation water to generate an organic-inorganic composite mineralized material, thereby achieving the purpose of plugging the low-permeability water-producing layer.

[0011] In order to solve the above technical problems, the preparation method of the low permeability oil reservoir water plugging agent with bionic mineralization of the present invention uses polyamino polypeptide, intermediate 1, intermediate 2 and intermediate 3 as raw materials, and the intermediate 1, intermediate 2 and intermediate 3 are respectively grafted on the polyamino polypeptide to obtain:

[0012]

[0013] Where R1 is R2 is R3 is

[0014] Furthermore, the molecular formula of the polyamino polypeptide is:

[0015]

[0016] Furthermore, the polyamino polypeptide is prepared by polycondensation of 1-chloroacetic acid and tetraethylenepentamine, and the process is as follows:

[0017]

[0018] Furthermore, the molecular formula of the intermediate 1 is:

[0019]

[0020] Furthermore, the intermediate 1 is prepared by polymerization of 5-aminouracil and ethylene glycol diglycidyl ether, and the process is as follows:

[0021]

[0022] Furthermore, the molecular formula of the intermediate 2 is:

[0023]

[0024] Further, the intermediate 2 is prepared by polymerization of p-aminocyclohexanone and ethylene glycol diglycidyl ether, and the process is as follows:

[0025]

[0026] Furthermore, the molecular formula of the intermediate 3 is:

[0027]

[0028] Further, the intermediate 3 is prepared by polymerization of sodium aminoethyl hypophosphite and ethylene glycol diglycidyl ether, and the process is as follows:

[0029]

[0030] The preparation method of the low permeability oil reservoir water plugging agent with bionic mineralization of the present invention uses 5-aminouracil, aminoethyl sodium hypophosphite, p-aminocyclohexanone, ethylene glycol diglycidyl ether, 1-chloroacetic acid, tetraethylene pentamine and nano calcium carbonate as raw materials, and sequentially comprises the following steps:

[0031] S1. Place 0.25 mol of tetraethylenepentamine into a 250 mL three-necked reaction flask with a condenser and a water separator, introduce nitrogen, add 0.25 mol of 1-chloroacetic acid solid powder in batches, keep the temperature below 30°C, stir and dissolve for 2 hours, then gradually heat to 110°C to initiate polymerization until no water flows out, which takes 4 hours, and cool to room temperature to obtain a light yellow solid for standby use;

[0032] S2, dissolve 0.05mol ethylene glycol diglycidyl ether in 30ml anhydrous ethanol, dissolve 0.05mol 5-aminouracil in 20ml anhydrous ethanol, and add 0.1g potassium hydroxide, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the drop is complete, let it stand at room temperature for 24 hours to obtain a yellow liquid for standby use;

[0033] S3, dissolve 0.05mol of ethylene glycol diglycidyl ether in 30ml of anhydrous ethanol, dissolve 0.05mol of p-aminocyclohexanone in 20ml of anhydrous ethanol, and add 0.3g of potassium hydroxide, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the dropwise addition, let it stand at room temperature for 24 hours to obtain a light yellow liquid for standby use;

[0034] S4, dissolve 0.05mol of ethylene glycol diglycidyl ether in 30ml of anhydrous ethanol, dissolve 0.05mol of aminoethyl sodium hypophosphite in 50ml of distilled water, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the dropwise addition, let it stand at room temperature for 24 hours to obtain a light yellow liquid for standby use;

[0035] S5, add the light yellow solid obtained in S1 to 200 ml of distilled water, stir to dissolve, add 0.5 g of potassium hydroxide, stir to dissolve, heat to 60°C, slowly add the liquids obtained in S2, S3 and S4 in turn, take 3 hours, then heat to 75°C, continue to react for 3 hours, cool to room temperature to obtain a yellow viscous liquid, add 300 ml of methanol, precipitate a white solid powder, filter, dry, crush and set aside;

[0036] S6. 15 g of nano calcium carbonate was mixed into the white solid powder obtained in S5, and dispersed by ultrasonic oscillation for 1 hour to obtain a white uniform solid powder.

[0037] Compared with the prior art, the present invention has achieved the following beneficial effects: the selective water plugging agent with biomimetic mineralization effect prepared by using 5-aminouracil, aminoethyl sodium hypophosphite, p-aminocyclohexanone, ethylene glycol diglycidyl ether, 1-chloroacetic acid, tetraethylenepentamine and nano calcium carbonate as raw materials can selectively plug the large water-producing pores of low-permeability fracture oil reservoirs, thereby resolving the contradiction that seriously affects the production of low-permeability oil fields. Among them, 1-chloroacetic acid and tetraethylenepentamine are used to generate polyamino polypeptides through polycondensation, and 5-aminouracil, aminoethyl sodium hypophosphite and p-aminocyclohexanone are grafted to obtain polypeptides containing functionalized side chain groups. Such polypeptides with hydrogen-donating groups and hydrogen-accepting groups at the end groups can self-assemble into a complex, thereby guiding the inorganic nanoparticles to assemble and precipitate, producing an effect similar to biomineralization, and generating an organic-inorganic composite mineral similar to animal bones. It is assembled and mineralized with nano calcium carbonate, calcium ions, carbonate ions and the like in the formation water in the low-permeability formation to generate an organic-inorganic composite mineralization layer, thereby plugging the fractures. In general, the water plugging agent can block strong water-producing fractures in low permeability reservoirs by simulating biomineralization, and has excellent water plugging effect. DETAILED DESCRIPTION

[0038] In order to make the technical means, creative features, objectives and effects of the present invention easier to understand, the present invention is further described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0040] Example 1

[0041] S1. Place 0.25 mol of tetraethylenepentamine into a 250 mL three-necked reaction flask with a condenser and a water separator, introduce nitrogen, add 0.25 mol of 1-chloroacetic acid solid powder in batches, keep the temperature below 30°C, stir and dissolve for 2 hours, then gradually heat to 110°C to initiate polymerization until no water flows out, which takes 4 hours, and cool to room temperature to obtain a light yellow solid for standby use;

[0042] S2, dissolve 0.05mol ethylene glycol diglycidyl ether in 30ml anhydrous ethanol, dissolve 0.05mol 5-aminouracil in 20ml anhydrous ethanol, and add 0.1g potassium hydroxide, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the drop is complete, let it stand at room temperature for 24 hours to obtain a yellow liquid for standby use;

[0043] S3, dissolve 0.05mol of ethylene glycol diglycidyl ether in 30ml of anhydrous ethanol, dissolve 0.05mol of p-aminocyclohexanone in 20ml of anhydrous ethanol, and add 0.3g of potassium hydroxide, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the dropwise addition, let it stand at room temperature for 24 hours to obtain a light yellow liquid for standby use;

[0044] S4, dissolve 0.05mol of ethylene glycol diglycidyl ether in 30ml of anhydrous ethanol, dissolve 0.05mol of aminoethyl sodium hypophosphite in 50ml of distilled water, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the dropwise addition, let it stand at room temperature for 24 hours to obtain a light yellow liquid for standby use;

[0045] S5, add the light yellow solid obtained in the above S1 to 200 ml of distilled water, stir to dissolve, add 0.5 g of potassium hydroxide, stir to dissolve, heat to 60°C, slowly add the liquids obtained in the above S2, S3 and S4 in sequence, take 3 hours, then heat to 75°C, continue to react for 3 hours, cool to room temperature to obtain a yellow viscous liquid, add 300 ml of methanol, precipitate a white solid powder, filter, dry, crush and set aside;

[0046] S6. 15 g of nano calcium carbonate was mixed into the white solid powder obtained in S5, and dispersed by ultrasonic oscillation for 1 hour to obtain a white uniform solid powder.

[0047] Example 2

[0048] Accurately weigh the white uniform solid powder prepared by S6 in Example 1, stir and disperse it in a solution with a mineralization degree of 10000 mg / L (where Ca 2+ The content of the sample is 100 mg / L) in simulated formation water, and ultrasonically oscillated for 3 hours at room temperature to prepare a colloidal solution with a sample concentration of 1.5% for 100g. Then it is placed in a constant temperature water bath, and the reaction is kept warm for 1 day, 3 days, 5 days, 7 days and 10 days, and then taken out, cooled to room temperature, the unreacted colloidal solution is filtered out, and the free and adsorbed precipitates on the cup wall are collected, and the precipitates are dried at a constant temperature of 105°C in a drying oven for 8 hours, taken out, weighed, and the mass percentage of the precipitate to the added white uniform solid powder sample is calculated, that is, the mineralization precipitation rate of the sample. The mineralization precipitation rates of the samples at three temperatures of 40°C, 60 and 80°C are measured according to the above method, see Tables 1 to 3.

[0049] Table 1 Mineralization precipitation rate of samples at 40℃

[0050]

[0051]

[0052] Table 2 Mineralization precipitation rate of samples at 60℃

[0053] Time, d Mass of sample added, g Mineralized sediment mass, g Mineralization precipitation rate, % 1 1.5000 0.3945 26.30 3 1.5000 0.7242 48.28 5 1.5000 0.8415 56.10 7 1.5000 0.8714 58.09 10 1.5000 0.8741 58.27

[0054] Table 3 Mineralization precipitation rate of samples at 80℃

[0055] Time, d Mass of sample added, g Mineralized sediment mass, g Mineralization precipitation rate, % 1 1.5000 0.6188 41.25 3 1.5000 0.8388 55.92 5 1.5000 0.9075 60.50 7 1.5000 0.9176 61.17 10 1.5000 0.9180 61.20

[0056] Example 3

[0057] Accurately weigh the white uniform solid powder sample prepared by S6 in Example 1, and use a mineralization degree of 10000 mg / L (including Ca 2+ Content is 100mg / L), 30000mg / L (including Ca 2+ Content is 300mg / L) and 50000mg / L (including Ca 2+ The colloidal solution with a sample concentration of 1.5% was prepared with simulated formation water (containing 500 mg / L), ultrasonically oscillated for 3 hours, and set aside; the cores with different porosities were placed in an incubator at 60°C for 3 hours; the core permeability was measured at a pump displacement of 1 ml / min; then the 1PV colloidal solution prepared above was reversely injected into the core, kept at 60°C for 7 days, and displaced with 60°C clean water until no colloidal solution flowed out; then the permeability of the core treated with the colloidal solution prepared with different mineralizations was measured at a pump displacement of 1 ml / min, and the permeability decrease rate of the treated core, that is, the plugging rate of the colloidal solution of the sample on the core, was calculated, see Tables 4 to 6.

[0058] Table 4 The plugging efficiency of colloidal solutions of samples with different mineralization configurations on low permeability cores (mineralization: 10000 mg / L, Ca 2+ :100mg / L))

[0059] Core porosity, % Original permeability, mDc Permeability after plugging, mDc Blockage rate, % 7.4 5.54 0.46 91.7 10.1 8.33 1.29 84.5 11.8 10.60 2.08 80.4

[0060] Table 5 The plugging efficiency of colloidal solutions of samples with different mineralization configurations on low permeability cores (mineralization: 30000 mg / L, Ca 2+ :300mg / L))

[0061] Core porosity, % Original permeability, mDc Permeability after plugging, mDc Blockage rate, % 7.3 5.20 0.29 94.4 9.9 8.18 1.05 87.2 12.1 11.39 1.98 82.6

[0062] Table 6 The plugging rate of colloidal solutions of samples with different mineralization configurations on low permeability cores (mineralization: 50000 mg / L, Ca2+: 500 mg / L)

[0063] Core porosity, % Original permeability, mDc Permeability after plugging, mDc Blockage rate, % 7.4 5.46 0.23 95.8 9.8 8.05 0.76 90.6 11.7 10.20 1.63 84.0

[0064] The above is only a preferred embodiment of the present invention, which shows and describes the basic principles, main features and advantages of the present invention, but does not limit the scope of patent protection of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. In addition to the above embodiments, the present invention may have other implementation modes without departing from the spirit and scope of the present invention. The present invention may also have various changes and improvements, and all technical solutions formed by equivalent substitution or equivalent transformation fall within the scope of protection required by the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents. The technical features not described in the present invention can be realized by or using existing technologies, which will not be repeated here.

Claims

1. A low permeability oil reservoir water plugging agent with bionic mineralization, characterized in that: It is formed by mixing a graft polymer with nano calcium carbonate, and the molecular formula of the graft polymer is: Where R1 is R2 is R3 is 2. A method for preparing a low-permeability oil reservoir water plugging agent with bionic mineralization, characterized in that: Using polyamino polypeptide, intermediate 1, intermediate 2 and intermediate 3 as raw materials, the intermediate 1, intermediate 2 and intermediate 3 are respectively grafted onto the polyamino polypeptide to obtain: Where R1 is R2 is R3 is 3. The method for preparing the low permeability oil reservoir water plugging agent with bionic mineralization according to claim 2, characterized in that: The molecular formula of the polyamino polypeptide is:

4. The method for preparing the low permeability oil reservoir water plugging agent with bionic mineralization according to claim 3, characterized in that: The polyamino polypeptide is prepared by polycondensation of 1-chloroacetic acid and tetraethylenepentamine, and the process is as follows:

5. The method for preparing the low permeability oil reservoir water plugging agent with bionic mineralization according to claim 2, characterized in that: The molecular formula of the intermediate 1 is:

6. The method for preparing the low permeability oil reservoir water plugging agent with bionic mineralization according to claim 5, characterized in that: The intermediate 1 is prepared by polymerization of 5-aminouracil and ethylene glycol diglycidyl ether, and the process is as follows:

7. The method for preparing the low permeability oil reservoir water plugging agent with bionic mineralization according to claim 2, characterized in that: The molecular formula of the intermediate 2 is:

8. The method for preparing the low permeability oil reservoir water plugging agent with bionic mineralization according to claim 7, characterized in that: The intermediate 2 is prepared by polymerization of p-aminocyclohexanone and ethylene glycol diglycidyl ether, and the process is as follows:

9. The method for preparing the low permeability oil reservoir water plugging agent with bionic mineralization according to claim 2, characterized in that: The molecular formula of the intermediate 3 is:

10. The method for preparing the low permeability oil reservoir water plugging agent with bionic mineralization according to claim 9, characterized in that: The intermediate 3 is prepared by polymerization of sodium aminoethyl hypophosphite and ethylene glycol diglycidyl ether, and the process is as follows:

11. A method for preparing a low permeability oil reservoir water plugging agent with bionic mineralization, characterized in that: The method is prepared from 5-aminouracil, sodium aminoethyl hypophosphite, p-aminocyclohexanone, ethylene glycol diglycidyl ether, 1-chloroacetic acid, tetraethylenepentamine and nano calcium carbonate as raw materials, and comprises the following steps in sequence: S1. Place 0.25 mol of tetraethylenepentamine into a 250 mL three-necked reaction flask with a condenser and a water separator, introduce nitrogen, add 0.25 mol of 1-chloroacetic acid solid powder in batches, keep the temperature below 30°C, stir and dissolve for 2 hours, then gradually heat to 110°C to initiate polymerization until no water flows out, which takes 4 hours, and cool to room temperature to obtain a light yellow solid for standby use; S2, dissolve 0.05mol ethylene glycol diglycidyl ether in 30ml anhydrous ethanol, dissolve 0.05mol 5-aminouracil in 20ml anhydrous ethanol, and add 0.1g potassium hydroxide, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the drop is complete, let it stand at room temperature for 24 hours to obtain a yellow liquid for standby use; S3, dissolve 0.05mol of ethylene glycol diglycidyl ether in 30ml of anhydrous ethanol, dissolve 0.05mol of p-aminocyclohexanone in 20ml of anhydrous ethanol, and add 0.3g of potassium hydroxide, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the dropwise addition, let it stand at room temperature for 24 hours to obtain a light yellow liquid for standby use; S4, dissolve 0.05mol of ethylene glycol diglycidyl ether in 30ml of anhydrous ethanol, dissolve 0.05mol of aminoethyl sodium hypophosphite in 50ml of distilled water, then slowly drop the above ethylene glycol diglycidyl ether ethanol solution at 20°C for 2 hours. After the dropwise addition, let it stand at room temperature for 24 hours to obtain a light yellow liquid for standby use; S5, add the light yellow solid obtained in S1 to 200 ml of distilled water, stir to dissolve, add 0.5 g of potassium hydroxide, stir to dissolve, heat to 60°C, slowly add the liquids obtained in S2, S3 and S4 in turn, take 3 hours, then heat to 75°C, continue to react for 3 hours, cool to room temperature to obtain a yellow viscous liquid, add 300 ml of methanol, precipitate a white solid powder, filter, dry, crush and set aside; S6. 15 g of nano calcium carbonate was mixed into the white solid powder obtained in S5, and dispersed by ultrasonic oscillation for 1 hour to obtain a white uniform solid powder.